Modelling Twitter conversations in #favela towards the conceptualization of the eVoice of the unheard. Issue 4 (19th March 2020) - Inversini, Alessandro; Williams, Nigel L.; Rega, Isabella; Samakovlis, Ioanna
Abstract : Purpose: The purpose of this study to shed light on the importance of social media hosted content related to socially-motivated discussions. Moving from the field of communication for development, the research leverages social media as a powerful tool for collecting and analyse peer-to-peer communication towards the conceptualization of eVoices of Unheard. The deep understanding of these conversation can generate recommendations for organizations and governments designing and providing interventions fostering local socio-economic development. Design/methodology/approach: The study presents a large-scale analysis of social media interactions on the topic "#favela" to generate insights into a social network structure, narrative contents and meaning generated. Findings: Structurally, the analysed networks are comparable with those presented in current academic literature; automatic text analysis confirmed the promise of the inner value of communication for development opening the floor to conceptualization of the "eVoices of unheard", which is the collective and conscious use of social media to mediate community discussions about tangible and intangible issues related to socio-economic development. Originality/value: Framed within the rise of interactive communication for development this research show that social media an support the notion of voice proposed by Couldry (2010) moving from process (i.e. the recording of the voice) towards value (i.e. the possibility of giving an account of one's life and its conditions to have an impact on human life and resources) thereby understanding intangible issues related with socio-economic development.